STUDY ON THE LOW-VELOCITY DYNAMIC RESPONSES OF PRE-STRESSED COMPOSITE PYRAMIDAL LATTICE STRUCTURES - XU JianXin; LUO YunFei; LI DingHe (Jixie qiangdu)
A finite element model is established for the pre-stressed composite pyramidal lattice structures. The influences of prestress on the contact force, contact duration, structural deformation, energy absorption and impact damages are investigated. Before subjected to low-velocity impact,the composite pyramidal lattice structure is pre-strained by the static responses. The numerical results indicate that pre-stress has no significant influence on the peak contact load,contact duration and rate of total energy absorption,while it plays an important role on the deformation. When the impact velocity is constant,the maximum displacement of impact center increases with increasing the tensile pre-stresses,but the maximum deformation of the bottom facesheet and the truss cores incline to decrease when tensile pre-stresses increase,while the effects of tensile pre-stresses on the structural deformation are otherwise.